O PRINCÍPIO DA IGUALDADE COMO FUNDAMENTO DOS DIREITOS HUMANOS DA MULHER - Carmen Silvia Lima de Arruda; Reis Friede (TRF2, 2018)
The protection and promotion of the Human Rights of Women is a responsibility of all the States that are signatories to the International Conventions that guarantee it. The objective of this study is to examine the evolution of the Human Rights of Women, a law coined under the prism of the principle of equality, a primordial source of democratic legitimization of public institutions. Following the analysis of the principle of equality itself, following the emergence of the concept of the Human Right of Women, with a brief retrospective of the International Conventions, the respective ratifications and vetoes of Brazil, to reach the scope of positive domestic law and finally, to proceed with the comparison of the decisions of the superior tribunals on this matter.